2005
DOI: 10.1093/ajcn/82.6.1185
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber intake and risk factors for cardiovascular disease in French adults

Abstract: Dietary fiber intake is inversely correlated with several cardiovascular disease risk factors in both sexes, which supports its protective role against cardiovascular disease and recommendations for its increased consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
169
3
25

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(207 citation statements)
references
References 40 publications
10
169
3
25
Order By: Relevance
“…Fibre may contribute to prevent weight gain, and consequently to reduce the risk of atherosclerosis. In fact, some studies assessing BMI instead of IMT as the main outcome have found inverse relationships, as we did between BMI and DF intake (Ludwig et al, 1999;Liu et al, 2003;Lairon et al, 2005;Bes-Rastrollo et al, 2006;Murakami et al, 2007). However, others did not find this association (Pietinen et al, 1996;Wu et al, 2003).…”
Section: Discussioncontrasting
confidence: 42%
“…Fibre may contribute to prevent weight gain, and consequently to reduce the risk of atherosclerosis. In fact, some studies assessing BMI instead of IMT as the main outcome have found inverse relationships, as we did between BMI and DF intake (Ludwig et al, 1999;Liu et al, 2003;Lairon et al, 2005;Bes-Rastrollo et al, 2006;Murakami et al, 2007). However, others did not find this association (Pietinen et al, 1996;Wu et al, 2003).…”
Section: Discussioncontrasting
confidence: 42%
“…This level is less than the value reported by Ishola et al [44] for Nigerian tamarind fruits. The zinc levels found were well below the FAO and WHO permissible level of 6 mg/100 g-fw [37].…”
Section: Heavy Metal Contentmentioning
confidence: 56%
“…Most crosssectional studies found an inverse association between fibre intake and body weight, which was confirmed by the few available longitudinal studies (Liu et al, 2003;Ludwig et al, 1999). More recent cross-sectional studies not included in the review by Slavin and conducted in France (Lairon et al, 2005) and Spain (Bes-Rastrollo et al, 2006) also observed inverse associations between fibre intake and BMI.…”
Section: Discussionmentioning
confidence: 85%